2020
DOI: 10.1177/0142331220909655
|View full text |Cite
|
Sign up to set email alerts
|

Observer-based event-triggered H∞ control for asynchronous switched delay systems

Abstract: In this paper, the [Formula: see text] performance of observer-based asynchronous linear switched delay systems with an event-triggered sampling scheme is considered. Firstly, owing to the system state cannot be measured completely in practice, a state feedback observer is used to reconstruct the system state. Next, we design an event-triggered sampling mechanism, under which the sample of the system only occur when the error exceeds a predetermined threshold, so it will reduce economic losses. Then, consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A switched system consists of a set of continuous (or discrete) time subsystems and the switching strategy between the subsystems (Liberzon, 2003; Sun and Ge, 2005). In the past few decades, the switched systems have attracted extensive attention due to both theoretical and practical reasons (Echreshavi and Roosta, 2018; Jin et al, 2019; Liu et al, 2019a, 2019b; Luo et al, 2020; Xiang et al, 2018; Xue et al, 2020; Yang et al, 2020; Zhao et al, 2017). The switched system plays an important role in many applications, such as aerospace systems Lian et al (2017) and networked control systems Deaecto et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…A switched system consists of a set of continuous (or discrete) time subsystems and the switching strategy between the subsystems (Liberzon, 2003; Sun and Ge, 2005). In the past few decades, the switched systems have attracted extensive attention due to both theoretical and practical reasons (Echreshavi and Roosta, 2018; Jin et al, 2019; Liu et al, 2019a, 2019b; Luo et al, 2020; Xiang et al, 2018; Xue et al, 2020; Yang et al, 2020; Zhao et al, 2017). The switched system plays an important role in many applications, such as aerospace systems Lian et al (2017) and networked control systems Deaecto et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…As a special networked control system, networked switched systems based on the communication network for packet transmission are turning into the hot research objects in the field of control (Ren et al, 2018; Tian et al, 2017). Networked switched systems can be utilized to model and describe the actual system with dynamic mutation caused by the change of production demand, the failure and recovery of system components (Long and Zhao, 2013; Sakthivel et al, 2015; Yan et al, 2019), and introduce the networked control technology to break the spatial restriction of the components of switched systems (Liberzon, 2014; Qi et al, 2018; Yang et al 2020b). Due to the openness of communication network, networked switched systems are vulnerable to malicious network attacks, resulting in packet dropout, delay, and so on (Amin et al, 2013; Zheng et al, 2019), thus the analysis and synthesis of such systems must be capable of handling these adverse situations.…”
Section: Introductionmentioning
confidence: 99%
“…Networked control systems (NCSs) are systems where components communicate with one another over a shared network (Lin et al, 2018). Thanks to the flexibility, low cost, easy installation and maintenance, applications of NCSs can be found in a wide range of fields (Li and Chen, 2019; Zhang et al, 2020b) and fruitful research results of control and filtering issues for NCSs have been reported in Yang et al (2020), Yan et al (2019) and Liu et al (2019). Communication efficiency, as one of the concerning issues in NCSs, has drawn considerable attentions from researchers in recent years.…”
Section: Introductionmentioning
confidence: 99%